Ionic Conductivity and Conduction Mechanism of Biodegradable Dual Polysaccharides Blend Electrolytes - K.H. Kamarudin; M.S.A. Rani; M.I.N. Isa (American-Eurasian Network for Scientific Information publisher, 2024)
Volume 9, Number 2